2014
DOI: 10.3109/14767058.2014.932768
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene study for smoking, alcohol use, and body weight in a sample of pregnant women

Abstract: Objective Prenatal smoking, alcohol use, and obesity have significant effects on maternal and fetal health. However, not much is known about the genetic contributions to these risk factors among pregnant women. We evaluate the associations between several candidate genes and smoking, alcohol use, pre-pregnancy body weight, and weight gain during pregnancy in a sample of pregnant women. Methods The study analyzes a sample of about 1,900 mothers from the Danish National Birth Cohort. We test the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Early pregnancy BMI was not associated with gene SNPs in our study. Out of four studies that examined an FTO association with prepregnancy BMI, three found an association [2, 8, 10]: in a Brazilian sample (primarily self-reported black skin) [2]; in a UK sample (unknown racial/ethnic group) [8]; and in Danish women [10]. In the fourth study, in a US African American sample no association was found [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early pregnancy BMI was not associated with gene SNPs in our study. Out of four studies that examined an FTO association with prepregnancy BMI, three found an association [2, 8, 10]: in a Brazilian sample (primarily self-reported black skin) [2]; in a UK sample (unknown racial/ethnic group) [8]; and in Danish women [10]. In the fourth study, in a US African American sample no association was found [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined obesity and diabetes genes on prepregnancy weight, GWG and/or weight retention [2, 610] with inconsistent findings due to variations in sample size, methodology, racial/ethnic sample composition, and candidate gene SNP selection. The FTO gene was associated with high prepregnancy BMI in a sample from Brazil (73.5% self-reported black/mixed) [2] and in a sample from the United Kingdom of unreported racial/ethnic groups [8].…”
Section: Introductionmentioning
confidence: 99%
“…While much of this genetic etiology remains unidentified, numerous studies have identified loci that are associated with in the general population. SNPs in FTO gene have been found significantly associated with pre-pregnancy obesity and body mass index in pregnant women [ 24 ]. Moreover, relationship between gene polymorphisms in PPARG [ 25 ] and overweight and obesity have also been reported.…”
Section: Introductionmentioning
confidence: 99%